COVID-19 Pandemic: An Unseen’s Evolution War - Song, Quek Yek; Ling, Michelle Jia Ni (Journal of Lumbini Medical College, 2020)
This is a new beginning. It started just like a fiction movie. In December 2019, a new cluster of pneumonia caused by the 2019 novel coronavirus (2019-nCoV) was first identified in Wuhan, China. Without any mercy, it became a pandemic and left no time for grief. It was not only life-threatening but also challenged our healthcare system, economy, culture, lifestyle and belief. It forced us to make changes. We need to evolve, and we must evolve. Malaysia, a multi-ethnicity and multireligious country which is located in Southeast Asia, has a population of 32 million with a median age of 28.9 years in 2019. According to the Observatory of Economic Complexity, Malaysia has experienced rapid globalization and is the 19th leading exporter in the world. It is an upper-middle-income country with a gross domestic product (GDP) of 370 billion USD in 2019, of which 4.5% is funded to the healthcare system.